Development of electronic kit for respiratory for detecting asthma - Cheow, Shek Hong (2017)
In this paper, a prototype of a carbon dioxide (C02) measurement device has designed to detect and monitor asthma patient. Nowadays, capnogram is widely uses in monitoring asthma and medical services. However, capnogram is costly and unaffordable for patient especially those in a low class family. Therefore, this low cost device is produced to detect and monitor the severity of asthma, this device can be owned by every class of family. Furthermore, spirometer and peak flow meter is well known in monitoring asthma. Unfortunately, these two devices have their own limitations as spirometer has complex procedures as the patient face difficulties on performing multiple criteria when using it and only suitable for age range above 6 years old. Meanwhile, flow meter will caused patient to have chest pain as they needed maximum effort to blow in the device. To overcome these limitations, this prototype electronic kit is easy to use and suitable for all range of patients. This prototype electronic kit consists of MH-Z14A C02 sensor to detect the concentration of C02 from exhaled air from user, Arduino microcontroller to process the data, TFT Display shield for data presentation and HC-06 Bluetooth module to communicate with PC for further analysis. This device was tested with 3 asthmatic and 3 normal users. The results showed that asthmatic user has a different graph pattern compared with normal user. This device has successfully distinguished the difference between asthmatic and normal user; therefore it is suitable for asthma monitoring.